2021
DOI: 10.3389/fneur.2020.620585
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNCA Parkinson's Disease Risk Polymorphisms With Disease Progression in Newly Diagnosed Patients

Abstract: Objectives: To evaluate the impact of SNCA polymorphisms originally identified as risk factors for Parkinson's disease (PD) on the clinical presentation and progression of the disease in a large cohort of population-based patients with incident PD.Methods: Four hundred thirty-three patients and 417 controls from three longitudinal cohorts were included in the study. Disease progression was recorded annually for up to 9 years using the Unified Parkinson's Disease Rating Scale (UPDRS) or Mini-Mental State Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…We show a small effect of rs356219 on global cognitive decline before adjustment for multiple comparisons, replicating our previous finding using a subset of 443 patients included in this current work. 30 A larger, independent cohort will be required to validate this result, but given the small effect size, the impact of this variant is unlikely to be clinically meaningful. Few studies have reported the impact of MAPT or rs356219 on the progression to dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We show a small effect of rs356219 on global cognitive decline before adjustment for multiple comparisons, replicating our previous finding using a subset of 443 patients included in this current work. 30 A larger, independent cohort will be required to validate this result, but given the small effect size, the impact of this variant is unlikely to be clinically meaningful. Few studies have reported the impact of MAPT or rs356219 on the progression to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…For primary analysis, patients were grouped by genotype based on previous studies: APOE , carriers of ε4 allele versus non‐carriers 6 ; GBA , carriers of any GBA mutation versus non‐carriers 6 ; MAPT , carriers of H1/H1 versus H2 haplotype 14 ; and SNCA rs356219, carriers of GG genotype versus A‐allele 30 . Primary analyses were corrected for multiple comparisons using the Benjamini–Hochberg false discovery rate (FDR) method at FDR < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, rs2870004 failed to reach significance in the Nalls et al ( 2019) meta-analysis. Like rs763443, the only other publication which references this SNP is the analysis of disease heterogeneity, and again they found that this SNP failed to explain any of the disease heterogeneity (Szwedo et al, 2020). GTEx data suggests that rs2870004 is not significantly correlated to SNCA or MMRN1 expression within the substantia nigra (Supplementary Table 2).…”
Section: Rs763443mentioning
confidence: 96%
“…The only other notable reference to this SNP is an analysis of disease heterogeneity based on genotype of the risk-signals identified by Pihlstrom et al (2018) . They found that this SNP failed to explain any of the disease heterogeneity amongst a large cohort of newly diagnosed PD patients ( Szwedo et al, 2020 ). According to GTEx, rs763443 does not significantly correlate to SNCA or MMRN1 expression in the substantia nigra ( Supplementary Table 2 ).…”
Section: The Snca Locusmentioning
confidence: 99%